Estimation of treatment effects in repeated public goods experiments - Jianning Kong; Donggyu Sul (Econometrics, 2018)
This paper provides a new statistical model for repeated voluntary contribution mechanism games. In a repeated public goods experiment, contributions in the first round are cross-sectionally independent simply because subjects are randomly selected. Meanwhile, contributions to a public account over rounds are serially and cross-sectionally correlated. Furthermore, the cross-sectional average of the contributions across subjects usually decreases over rounds. By considering this non-stationary initial condition-the initial contribution has a different distribution from the rest of the contributions-we model statistically the time varying patterns of the average contribution in repeated public goods experiments and then propose a simple but efficient method to test for treatment effects. The suggested method has good finite sample performance and works well in practice.
Keywords: C91; C92; C33; 330; repeated public goods games; asymptotic treatment effects; trend regression